Co-delivery of honokiol, a constituent of Magnolia species, in a self-microemulsifying drug delivery system for improved oral transport of lipophilic sirolimus. (1st September 2016) - Ding, Weiming; Hou, Xucheng; Cong, Shuangchen; Zhang, Yuanyuan; Chen, Mengmeng; Lei, Jiongxi; Meng, Yansha; Li, Xinru; Li, Guiling
Abstract: Sirolimus is recognized as a P-glycoprotein (P-gp) substrate with poor water-solubility. To improve its solubility and bioabsorption, self-microemulsifying drug delivery systems (SMEDDS) containing a novel P-gp inhibitor, honokiol, were prepared. The aim of this work was to evaluate the enhanced transport of sirolimus SMEDDS as well as the roles of honokiol. In situ single-pass intestinal perfusion and in vitro human colon adenocarcinoma (Caco-2) cell models were applied to study the effects of honokiol within SMEDDS on the transport of sirolimus. The results indicated that a combination of honokiol with sirolimus in SMEDDS did not significantly alter the particle size, polydispersity index and release of drugs. In addition, the absorption rate constant ( K a ) as well as the effective permeability coefficients ( P eff ) of sirolimus in situ intestinal absorption, and the apparent permeability coefficients ( P app ) of sirolimus in caco-2 cells were significantly enhanced by cremophor EL-based SMEDDS with honokiol as compared with those of SMEDDS without honokiol. Rhodamine123 uptake rate in caco-2 cells and in vitro cytotoxicity of sirolimus were enhanced by honokiol in SMEDDS indicating a substantial P-gp inhibition of honokiol. In conclusion, coadministration of honokiol with poor soluble P-gp substrate in SMEDDS, could serve as a favorable approach for oral delivery.